Gel-type composition for external use on skin
The gel-like external skin composition, combining L-ascorbic acid derivatives with nonionic synthetic water-soluble polymers and natural water-soluble polysaccharides, addresses the challenges of shape retention, feel, and stability, resulting in a composition that is both effective and cost-efficient.
Patent Information
- Application Number
- JP2021518389
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-07
- Filing Date
- 2020-05-01
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-05-01
AI Technical Summary
Existing gel-like external skin compositions containing L-ascorbic acid derivatives face challenges with shape retention, feel, and stability, particularly when salts are generated or when a salt-like form of the ascorbic acid derivative is desired.
A gel-like external skin composition is formulated using an L-ascorbic acid derivative, a nonionic synthetic water-soluble polymer such as (PEG-240/decyltetradeceth-20/HDI) copolymer, and a natural water-soluble polysaccharide, which together enhance shape retention, feel, and stability.
The composition achieves excellent shape retention, feel, and stability, allowing for continuous daily use on the skin without discomfort, and is industrially producible at a low cost.
Smart Images

Figure 0007665510000001 
Figure 0007665510000002 
Figure 0007665510000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a gel composition for external use on the skin, and more particularly to a gel composition for external use on the skin that contains an L-ascorbic acid derivative and has excellent shape retention, a pleasant feel when used, and stability. [Background technology]
[0002] L-ascorbic acid and L-ascorbic acid derivatives are known to exert a wide range of effects on the skin, including whitening effects, collagen production promotion effects, antioxidant effects, etc. Among these effects, compositions for topical application to the skin containing L-ascorbic acid derivatives have long been in practical use, and are widely used by people of all ages, from young to elderly, with the aim of achieving whitening effects in particular.
[0003] Among these, gel-type compositions for topical skin application have the properties of having high water-retaining capacity, retaining a large amount of moisture, and being able to incorporate a good balance of moisture and oil. Therefore, they can provide the moisturizing effect strongly desired for a topical skin application composition, and can be relatively easily incorporated with aqueous or oil-based cosmetic ingredients. For these reasons, many gel-type preparations for topical skin application have been put to practical use, including gel lotions, gel emulsions, gel beauty serums, gel creams, gel packs, gel sunscreens, gel cleansers, and gel foundations.
[0004] Gel-type skin topical compositions commonly used in the fields of cosmetics and pharmaceuticals contain thickeners to improve the feel and stability of the composition. For example, water-soluble synthetic carboxyvinyl polymers have high viscosity, form gels, and maintain their shape. When applied to the skin, they easily disintegrate while maintaining a moist feeling, and provide a non-sticky feel. Therefore, they are widely used to thicken the base of skin care preparations. However, they have the drawback of having low salt tolerance, and when salt is added, the viscosity drops significantly, causing the gel to collapse.
[0005] Increasing the concentration of carboxyvinyl polymer to compensate for the decrease in viscosity of carboxyvinyl polymer due to salt causes stickiness and sagging (residue of polymer compound), significantly impairing the feel when used. For this reason, in gel-type skin topical compositions containing L-ascorbic acid derivatives, it has been difficult to design a carboxyvinyl polymer-containing formulation that aims to maintain the shape of a gel, for example, when a salt is generated during neutralization of the ascorbic acid derivative or when an ascorbic acid derivative in the form of a salt is to be incorporated.
[0006] On the other hand, in gel-type skin topical compositions containing ascorbic acid derivatives, the use of an associative thickener with a hydrophobic group introduced at the end of a nonionic water-soluble polymer chain has been proposed to avoid the effect of salt on shape retention (Patent Document 1). This associative thickener is a nonionic hydrophobically modified polyurethane, which, unlike carboxyvinyl polymers, thickens through intermolecular and intramolecular hydrophobic interactions. Therefore, it is said to be largely unaffected by salt and capable of incorporating high concentrations of salt. On the other hand, gel-type skin topical compositions containing nonionic hydrophobically modified polyurethane have the disadvantage that when filled in a container or the like and attempted to be dispensed with fingers, the formulation does not adhere well to the fingers, resulting in poor "finger-smearing." Furthermore, the texture of the composition, such as its spreadability on the skin and its refreshing feeling, was not fully satisfactory.
[0007] It has also been proposed to use a natural water-soluble polysaccharide as a thickener in a gel composition for topical skin application containing an ascorbic acid derivative (Patent Document 2). Although the formulation becomes a viscous solution by incorporating a natural water-soluble polysaccharide, gelation is difficult, and the texture is thick and not refreshing, resulting in an unsatisfactory feel.
[0008] Furthermore, in order to avoid the effect of salts on shape retention in gel-type skin topical compositions containing ascorbic acid derivatives, the use of alkyl-modified carboxyvinyl polymers (Patent Document 3), the use of a combination of lysophospholipids and glycerin monoalkyl ethers (Patent Document 4), the use of polyacrylic acid derivatives (Patent Document 5), and the use of cross-linked hyaluronic acid gels (Patent Document 6) have been proposed. However, these proposals are not fully satisfactory in terms of shape retention, usability, etc., and there is still a demand for thickening bases that offer excellent shape retention and usability in gel-type skin topical compositions containing ascorbic acid derivatives.
[0009] Furthermore, in recent years, there has been a trend toward preference for topical skin compositions in the weakly acidic to neutral range, which is close to the skin's pH range. Furthermore, in the alkaline range of pH 7.5 or higher, there are concerns about discoloration and decomposition of preservatives such as parabens, which are essential for aqueous preparations, and odor changes of moisturizing ingredients. Many salt-type drugs, such as ascorbic acid derivatives, lose their stability in the alkaline range. Therefore, for gel-type topical skin compositions, a thickener that is stable, has high shape retention, and provides an excellent feel in use in the pH range of 5.0 to 7.0 is desired.
[0010] As mentioned above, L-ascorbic acid derivatives have whitening effects and are very useful ingredients. However, gel compositions for topical skin application containing these have problems with respect to texture, such as shape retention, freshness, spreadability on the skin, finger runnyness, and smudging, and these problems have not yet been resolved. A gel composition for topical skin application containing an L-ascorbic acid derivative and having fully satisfactory shape retention, texture, and stability has not yet been obtained. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Laid-Open No. 2005-68023 [Patent Document 2] Japanese Patent Application Publication No. 2018-131471 [Patent Document 3] Japanese Patent Application Laid-Open No. 2005-132828 [Patent Document 4] Japanese Patent Application Laid-Open No. 2010-202605 [Patent Document 5] Japanese Patent Application Laid-Open No. 2004-075672 [Patent Document 6] Japanese Patent Application Laid-Open No. 2010-202522 Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made in view of the above-mentioned prior art, and the problem to be solved is to provide a gel-type composition for topical skin application that contains an L-ascorbic acid derivative and has fully satisfactory shape retention, feel when used, and stability. In particular, the present invention aims to provide a gel-type composition for topical skin application that has fully satisfactory shape retention, feel when used, and stability without being affected by L-ascorbic acid derivatives and their salts, even when the composition is required to contain them, or when it is expected that salts will be generated by neutralization in order to adjust the pH of the gel-type composition for topical skin application to a pH range from slightly acidic to approximately neutral. [Means for solving the problem]
[0013] In order to solve the above problems, the inventors have conducted extensive research and have conducted preliminary tests using ionic synthetic water-soluble polymers, such as various carboxyvinyl polymers and various acrylic acid / methacrylic acid copolymers, which are commonly used as gel bases in topical skin compositions, as well as combining these with other materials.As a result, the problem of reduced shape retention of compositions containing L-ascorbic acid derivatives could not be resolved, and they have concluded that it is difficult to solve the above problems by combining ionic synthetic water-soluble polymers with L-ascorbic acid derivatives.
[0014] Therefore, the inventors conducted a comparative study of combinations of L-ascorbic acid derivatives with non-ionic water-soluble polymers such as (PEG-240 / decyltetradeceth-20 / HDI) copolymers, and found that although the problem of reduced shape retention was resolved or significantly reduced, problems with the feel of the product when used, such as poor spreadability on the skin, poor finger feel, and creasing, still occurred.
[0015] Next, the inventors conducted extensive comparative studies to determine whether it would be possible to solve the problems of use, such as poor spreadability on the skin, poor finger feel, and creasing, by combining a composition of an L-ascorbic acid derivative and a non-ionic synthetic water-soluble polymer such as a (PEG-240 / decyltetradeceth-20 / HDI) copolymer with other materials.
[0016] As a result, it was discovered, quite unexpectedly, that by further combining a natural water-soluble polysaccharide or a derivative thereof, problems with the feel of use, such as poor spreadability on the skin, poor finger feel, and creasing, can be eliminated or reduced, and further, the composition can be used as a gel-type topical skin composition that is excellent in stability and meets the intended purpose.
[0017] That is, the present invention solves the above-mentioned problems by providing a gel-like composition for topical application to the skin containing an L-ascorbic acid derivative, a nonionic synthetic water-soluble polymer, and a natural water-soluble polysaccharide. [Effects of the Invention]
[0018] The topical skin gel composition of the present invention is a skin gel composition containing an L-ascorbic acid derivative, a nonionic synthetic water-soluble polymer, and a natural water-soluble polysaccharide, which can be applied to the skin, etc., safely, easily, and continuously on a daily basis by humans without discomfort, and which can be provided industrially at low cost. Even when containing an L-ascorbic acid derivative that exerts various physiological functions, the topical skin gel composition of the present invention is useful as a skin gel composition that properly maintains these physiological functions, has excellent shape retention and stability of the formulation, and has a significantly excellent feel when used. DETAILED DESCRIPTION OF THE INVENTION
[0019] Hereinafter, embodiments of the present invention will be described, but these are merely examples of preferred modes for carrying out the present invention, and the present invention is not limited to these embodiments in any way.
[0020] The present invention relates to a gel composition for external use on the skin, which contains an L-ascorbic acid derivative, a nonionic synthetic water-soluble polymer, and a natural water-soluble polysaccharide.
[0021] The gel composition for topical skin application of the present invention contains an L-ascorbic acid derivative and salts produced by neutralizing the acid and base in the composition, but this does not affect its shape retention or stability and provides an excellent feel when used.
[0022] The L-ascorbic acid derivatives referred to in this specification are not particularly limited as long as they are themselves more stable than L-ascorbic acid, liberate L-ascorbic acid in vivo, and exhibit the inherent functions of L-ascorbic acid. Examples of L-ascorbic acid derivatives that can be used as components of the present invention include glycosyl derivatives, acylated derivatives, and phosphorylated derivatives of L-ascorbic acid.
[0023] As glycosyl derivatives of L-ascorbic acid, derivatives in which a glycosyl group is bonded to the hydroxyl group at the 2-position of L-ascorbic acid are preferably used because of their high stability. Examples of such derivatives include 2-O-α-glycosyl-L-ascorbic acid (ascorbic acid 2-glycoside), in which a series of glycosyl groups such as glucosyl, maltosyl, and maltotriosyl are bonded to the hydroxyl group at the 2-position of L-ascorbic acid via α-bonding, as disclosed in JP-A-3-135992 and JP-A-3-139288, and 2-O-β-D-galactosyl-L-ascorbic acid (ascorbic acid 2-galactoside), in which a galactosyl group is bonded to the hydroxyl group at the 2-position of L-ascorbic acid via β-bonding, as disclosed in JP-A-6-263790.
[0024] Examples of acylated derivatives of L-ascorbic acid (fatty acid ester derivatives) include ascorbic acid palmitate, ascorbic acid dipalmitate, ascorbic acid tetrahexyldecanoate, and ascorbic acid cholesterol ester, as disclosed in JP-A Nos. 59-10505, 63-104971, 6-247956, and 2004-331524. Examples of phosphorylated derivatives of L-ascorbic acid include ascorbic acid 2-phosphate and various metal salts thereof, as disclosed in JP-A Nos. 61-152613, 5-339123, 2002-3330, and 2006-63060.
[0025] Among the various L-ascorbic acid derivatives mentioned above, glycosyl derivatives of L-ascorbic acid are highly stable and are most preferred. Among these, 2-O-α-D-glucosyl-L-ascorbic acid (hereinafter abbreviated as "ascorbic acid 2-glucoside"), in which a glucosyl group is α-linked to the hydroxyl group at the 2-position of L-ascorbic acid, is the most suitable. Ascorbic acid 2-glucoside is a safe and versatile substance that has been widely used as an ingredient in various foods and beverages, cosmetics, quasi-drugs, pharmaceuticals, and other products. Furthermore, ascorbic acid 2-glucoside is a derivative of L-ascorbic acid developed to address the instability of L-ascorbic acid. It exhibits the revolutionary properties of not exhibiting direct reduction, being stable, and having excellent shelf life. Furthermore, in vivo, it is decomposed into L-ascorbic acid and D-glucose by the action of endogenous enzymes, thereby exhibiting the inherent physiological activity of L-ascorbic acid. As disclosed in, for example, Japanese Patent Application Laid-Open Nos. 3-135992 and 3-139288, ascorbic acid 2-glucoside is produced inexpensively on an industrial scale by treating a solution containing L-ascorbic acid and starch with cyclomaltodextrin glucanotransferase as a glycosyltransferase, and then treating the resulting ascorbic acid 2-glycoside with glucoamylase.
[0026] Ascorbic acid 2-glucoside is preferably used in a partially or completely crystalline form. It is known that anhydrous crystalline ascorbic acid 2-glucoside exists, and can be preferably used in the present invention. Examples of crystalline ascorbic acid 2-glucoside include the powder containing anhydrous crystalline 2-O-α-D-glucosyl-L-ascorbic acid disclosed in the aforementioned Japanese Patent Application Laid-Open No. 3-135992 and International Publication No. WO 2012 / 121297. A commercially available product is a powder containing anhydrous crystalline ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)", Hayashibara Sales Co., Ltd.), which is sold as a cosmetic and quasi-drug ingredient.
[0027] The L-ascorbic acid derivative used in the gel-type topical skin composition of the present invention may be in the form of a salt, as long as it dissociates in an aqueous medium. Examples of salts suitable for use in the gel-type topical skin composition of the present invention include sodium, potassium, aluminum, and zinc salts of ascorbic acid 2-glucoside. For example, the sodium salt of ascorbic acid 2-glucoside can be obtained by neutralizing an aqueous solution of ascorbic acid 2-glucoside with an alkali such as sodium hydroxide and then drying. When dissolved in an aqueous medium, the sodium salt of ascorbic acid 2-glucoside at least partially dissociates into ascorbic acid 2-glucoside anion and sodium ion, depending on the pH. Therefore, similar to ascorbic acid 2-glucoside, it is particularly suitable for use in the present invention.
[0028] The term "nonionic synthetic water-soluble polymer" as used herein refers to a nonionic synthetic water-soluble polymer obtained by chemical synthesis using petroleum as a raw material, etc. Suitable specific examples include vinyl-based polymers such as polyvinyl alcohol, polyvinylpyrrolidone, and polyvinyl methyl ether, as well as (PEG-240 / decyltetradeceth-20 / HDI) copolymer, polyurethane, polyethylene oxide, ethylene oxide-propylene oxide block copolymer, polymeric silicone, and derivatives thereof.
[0029] Among these, (PEG-240 / decyltetradeceth-20 / HDI) copolymer, polyurethane, polyvinyl alcohol, ethylene oxide-propylene oxide block copolymer, and derivatives thereof can be more preferably used.
[0030] The term "natural water-soluble polysaccharides" as used herein refers to water-soluble polymers that are natural products and / or polysaccharides derived from natural products, and includes those obtained by chemically and enzymatically modifying these. The origin of the natural products is not limited, and they may be derived from plants, microorganisms, animals, or seaweed, for example. Preferred examples include guar gums such as guar gum, cationized guar gum, carboxymethyl-hydroxypropylated guar gum, and hydroxypropylated guar gum; quince seed gum; mannan; tamarind gum; tara gum; soluble dextrin; locust bean gum; gum arabic; ghatti gum; karaya gum; tragacanth gum; arabinogalactan; pectin; quince; and cationized cellulose, methylcellulose, ethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, and carboxypropylmethylcellulose. Examples of suitable polymers include plant-derived polymers such as soluble cellulose, soluble starches such as carboxymethyl starch, methyl starch, starch phosphate esters, and sodium starch glycolate, and derivatives and salts thereof; animal-derived polymers such as chitosan, hyaluronic acid, chondroitin sulfate, derivatives and salts thereof; microbial-derived polymers such as curdlan, xanthan gum, gellan gum, cyclodextrin, dextran, pullulan, succinoglucan, derivatives and salts thereof; and seaweed-derived polymers such as alginic acid, carrageenan, agar, agarose, furcellan, propylene glycol alginate, derivatives and salts thereof.
[0031] Among these, soluble cellulose, xanthan gum, guar gum, tamarind gum, locust bean gum, soluble starch, soluble dextrin, cyclodextrin, pullulan, derivatives thereof, and salts thereof can be more preferably used.
[0032] The mass ratio of the L-ascorbic acid derivative, nonionic synthetic water-soluble polymer, and natural water-soluble polysaccharide contained in the gel-type skin composition of the present invention, based on dry solids, is preferably 1:0.01-500:0.01-500, more preferably 1:0.05-200:0.02-100, and even more preferably 1:0.1-100:0.05-50. A ratio below the lower limit or above the upper limit is undesirable because the desired effects may be significantly reduced or may not be achieved. Specifically, when the nonionic synthetic water-soluble polymer contained in the gel-type skin composition of the present invention is contained in an amount exceeding this range, the gel-type skin composition for topical use generally suffers from poor texture, such as creasing, while a ratio below this range results in poor shape retention, which is undesirable. Generally, if the amount of natural water-soluble polysaccharide contained in the gel composition for topical skin of the present invention exceeds this range, the gel composition for topical skin will be sticky and have a poor feel when used, and if the amount is below this range, the gel composition for topical skin will not be able to achieve the effect of improving the feel to the touch and will have a poor feel when used, which is undesirable.
[0033] The gel-type composition for topical skin application of the present invention can be used alone, but it is preferable to add appropriate commonly used cosmetic ingredients to it and use it as various cosmetics depending on the intended use. For example, the gel-type composition for topical skin application of the present invention can be made into a gel-type lotion by adding ethanol or a moisturizer to it. Such a gel-type lotion can further contain one or more astringents, keratin softeners, emollients, or surfactants. Furthermore, one or more fragrances, dyes, preservatives or bactericides, UV absorbers or UV scattering agents, sequestering agents, buffers (pH adjusters), antioxidants, whitening agents, anti-inflammatory agents, blood circulation promoters, thickeners, vitamins, amino acids, cell activators, transdermal absorption promoters, solubilizers, pigments, and other ingredients can be optionally added. Those generally usable in topical skin applications, including cosmetics, can be used. In addition to these, existing cosmetic ingredients can also be used. For example, "Standards for Cosmetic Ingredients, Second Edition, Commentary," edited by the Japan Compendium Association, published by Yakuji Nipposha Co., Ltd. in 1984; "Standards for Ingredients Other Than the Standards for Cosmetic Ingredients," supervised by the Inspection Division of the Pharmaceutical Affairs Bureau, Ministry of Health and Welfare, published by Yakuji Nipposha Co., Ltd. in 1993; "Supplement to the Standards for Ingredients Other Than the Standards for Cosmetic Ingredients," supervised by the Inspection Division of the Pharmaceutical Affairs Bureau, Ministry of Health and Welfare, published by Yakuji Nipposha Co., Ltd. in 1993; "Approval Standards for Cosmetics by Type," supervised by the Inspection Division of the Pharmaceutical Affairs Bureau, Ministry of Health and Welfare, published by Yakuji Nipposha Co., Ltd. in 1993; ", supervised by the Inspection Division of the Pharmaceutical Affairs Bureau of the Ministry of Health and Welfare, published by Yakuji Nippo Co., Ltd. in 1997; "Latest Cosmetic Science - Revised and Enlarged II," edited by the Association of Japanese Cosmetic Chemists, published by Yakuji Nippo Co., Ltd. in 1992; "Cosmetics Encyclopedia," edited by the Association of Japanese Cosmetic Chemists, published by Maruzen Co., Ltd. in 2003; and "Japanese Cosmetic Raw Materials Collection 2007," edited by the Japan Cosmetic Industry Association, published by Yakuji Nippo Co., Ltd. in 2007.
[0034] The amount of the aforementioned commonly used cosmetic ingredients in the gel composition for external use on skin of the present invention may be any amount as long as the desired effect is achieved. As a method for incorporating the ingredients, one or more known methods such as mixing, kneading, blending, adding, dissolving, immersing, penetrating, scattering, applying, spraying, and injecting may be appropriately used in the process leading up to the completion of the composition.
[0035] The gel composition for topical skin application of the present invention can be suitably used in the field of cosmetics such as skin care cosmetics, makeup cosmetics, and hair care cosmetics, and is expected to have excellent effects particularly when incorporated into skin care cosmetics that are applied directly to the skin, such as lotions, facial cleansers, serums, emulsions, creams, etc. The gel composition for topical skin application of the present invention can also be optionally incorporated into other cosmetics, quasi-drugs, or pharmaceuticals.
[0036] The present invention is further illustrated by the following experiments.
[0037] <Experiment 1: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative and evaluation of its properties and usability> Tests were conducted on the shape retention and usability of gel compositions for external use on the skin containing L-ascorbic acid derivatives.
[0038] <Experiment 1-1: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative> An ascorbic acid derivative-containing gel composition for topical skin application was prepared according to the formulation shown in Table 1, using ascorbic acid 2-glucoside as the ascorbic acid derivative, (PEG-240 / decyltetradeceth-20 / HDI) copolymer as the nonionic synthetic water-soluble polymer, and a cellulose derivative as the natural water-soluble polysaccharide.
[0039] A glass container was charged with 215 g of deionized water, and then 20 g of PEG-240 / decyltetradeceth-20 / HDI copolymer (trade name "ADEKA NOL GT-730" (sold by ADEKA Corporation)) and 15 g of pentylene glycol (Hydrolite-5, manufactured by Symrise Co., Ltd.) as a preservative were added. The mixture was mixed at 300 rpm using a Three-One Motor (BL1200, manufactured by Yamato Scientific Co., Ltd.) to prepare an aqueous solution of a nonionic synthetic water-soluble polymer (dry solids concentration of PEG-240 / decyltetradeceth-20 / HDI copolymer: 2.4% by mass) (hereinafter referred to as "aqueous solution of a nonionic synthetic water-soluble polymer"). ADEKA NOL GT-730 is a mixture of 30% by mass of PEG-240 / decyltetradeceth-20 / HDI copolymer, 50% by mass of butylene glycol, and 15% by mass of water. The liquid composition was composed of 19.94% by mass of cellulose acetate, 0.03% by mass of potassium laurate, and 0.03% by mass of tocopherol. Next, 225 g of deionized water heated to 70°C was placed in another glass container, and 25 g of stearoxyhydroxypropylmethylcellulose (trade name "Sangelose 60L" (sold by Daido Chemical Industry Co., Ltd.)) was added. The mixture was stirred for 1 minute using a stirrer, and then stirred for 30 minutes while cooling with ice water to prepare an aqueous solution of natural water-soluble polysaccharide (stearoxyhydroxypropylmethylcellulose concentration: 10.0% by mass). (Hereinafter referred to as "natural water-soluble polysaccharide aqueous solution"). Furthermore, 20 g of powder containing anhydrous crystals of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)", Hayashibara Co., Ltd.) was added to 100 g of deionized water and dissolved using a stirrer. Subsequently, 20 g of citrate buffer (1% by mass of citric acid, 15% by mass of sodium citrate) and 24.7 g of 10% by mass of sodium hydroxide were added to neutralize the ascorbic acid 2-glucoside (total amount 164.7 g, hereinafter referred to as "neutralized aqueous solution of ascorbic acid 2-glucoside").Each composition was prepared by placing 30 g of deionized water in a separate glass container, adding an aqueous solution of a nonionic synthetic water-soluble polymer and an aqueous solution of a natural water-soluble polysaccharide to obtain the formulation shown in Table 1, followed by adding 32.94 g of a neutralized aqueous solution of ascorbic acid 2-glucoside, and while mixing with a spatula, adding an appropriate amount of 10% by mass sodium hydroxide. The pH was adjusted to around 6.0 using a pH meter (F-74, manufactured by Horiba, Ltd.), and then adding water to make up the total volume to 200 g, thereby preparing gel-type compositions for external use on the skin 1 to 8 (hereinafter simply referred to as "compositions 1 to 8").
[0040] The formulations of Compositions 1 to 8 are shown in Table 1. Specifically, for Compositions 1 to 7, the amount of (PEG-240 / decyltetradeceth-20 / HDI) copolymer was the same (1.2% by mass), and the amount of stearoxyhydroxypropylmethylcellulose was varied to 0, 0.1, 0.2, 0.3, 0.5, 1, or 5% by mass. Furthermore, for Composition 8, no (PEG-240 / decyltetradeceth-20 / HDI) copolymer was blended, and 5% by mass of stearoxyhydroxypropylmethylcellulose was blended.
[0041] Controls 1 and 2 were prepared as follows, with the formulations shown in Table 1. Specifically, Controls 1 and 2 were prepared in the same manner as Compositions 1 to 8, except that instead of the (PEG-240 / decyltetradeceth-20 / HDI) copolymer as the nonionic synthetic water-soluble polymer, 0.5% by mass of a carboxyvinyl polymer or 0.5% by mass of an acrylic acid alkyl methacrylate copolymer, which are ionic synthetic water-soluble polymers, were blended, and no stearoxyhydroxypropylmethylcellulose was blended as the natural water-soluble polysaccharide. The carboxyvinyl polymer and acrylic acid alkyl methacrylate copolymer were blended by previously preparing an "ionic synthetic water-soluble polymer aqueous solution" containing the carboxyvinyl polymer or the acrylic acid alkyl methacrylate copolymer, and using this in place of the "nonionic synthetic water-soluble polymer aqueous solution." The "ionic synthetic water-soluble polymer aqueous solution" was prepared as follows: Specifically, 215 g of deionized water heated to 45°C was placed in a glass container, and then 2.5 g of a carboxyvinyl polymer (trade name "AQUPEC HV-505" (sold by Sumitomo Seika Chemicals Co., Ltd.) or an acrylic acid methacrylate alkyl copolymer (trade name "Carbopol Ulyrez10 Polymer" (sold by Lubrizol Advanced Materials)) and 15 g of pentylene glycol as a preservative were added. The mixture was mixed using a stirrer with the pH set to 4. An appropriate amount of 10% by mass sodium hydroxide was added, and the pH was adjusted to around 6.0 using a pH meter. Water was then added to bring the total volume to 250 g, preparing an aqueous solution of an ionic synthetic water-soluble polymer (solids concentration: 1.0% by mass).
[0042] Controls 3 and 4 were prepared in the same manner as Compositions 1 to 8, except that 1% by mass of the oligosaccharide sorbitol or 1% by mass of trehalose was blended instead of stearoxyhydroxypropylmethylcellulose as the natural water-soluble polysaccharide, based on the formulation shown in Table 1. Specifically, 225 g of deionized water was placed in a glass container, and then 25 g of sorbitol (trade name "Sorbitol Kao", sold by Kao Corporation) or trehalose (trade name "Trehalose (for cosmetics)", sold by Hayashibara Co., Ltd.) was added and stirred for 1 minute using a stirrer to prepare an aqueous solution of oligosaccharides, which was used in place of the aqueous solution of natural water-soluble polysaccharides.
[0043] <Experiment 1-2: Evaluation of the properties of a gel-type skin topical composition containing an L-ascorbic acid derivative> The properties and feel of use of Compositions 1 to 8 and Controls 1 to 4 (hereinafter referred to as "each composition") obtained in Experiment 1-1 were evaluated, and the results are summarized in Table 2.
[0044] The properties of each composition were evaluated using shape retention as an index. Immediately after preparation, 110 mL of each composition was filled into a transparent glass screw-cap bottle (No. 8, Maruemu Co., Ltd.) with a diameter of 4 cm and a height of 12 cm. After leaving the bottle standing overnight, the bottle was tilted 45° from vertical to horizontal, and the change in shape of each composition, i.e., shape retention, was observed with the naked eye. Compositions that are not salt-tolerant and do not form a gel become unstable, and therefore flow due to the change in gravity when the bottle is tilted. This test and evaluation serve as an index of the aesthetic appearance of a composition that has formed a gel when filled in a cosmetic container. The properties of each composition were visually observed and rated on a three-level scale based on the following criteria. (Criteria for determining automorphism) ◯: When the container is tilted, the composition maintains its shape, or the composition deforms but does not exhibit flowability. △: When the container is tilted, the composition deforms and has a gentle fluidity. ×: When the container is tilted and the lid is opened, the liquid is so fluid that it spills out.
[0045] The feel of each composition (freshness, spreadability on the skin, and smudging) was evaluated by five trained panelists (two men and three women) using compositions prepared in the same manner as in Experiment 1-1 and left to stand overnight. The measurement site was the inner forearm of each panelist. 0.5 g of each composition was placed on the inner forearm of each panelist, and spread with the fingertips of the other hand. A sensory evaluation was conducted on the freshness and spreadability on the skin immediately after spreading. Each composition was also evaluated by moving the finger back and forth until it dried, and the presence or absence of smudging. Furthermore, a sensory evaluation was conducted on the amount of each composition adhering to the finger using another finger. The feel of use was judged on a three-point scale based on the following criteria. (Criteria for determining freshness) ○: Four or more panelists rated it as having a fresh texture. △: 2 or more and 3 or less panelists evaluated the texture as fresh and moist. ×: One or less panelists evaluated the texture as fresh. (Criteria for assessing spreadability on skin) ○: Four or more panelists rated it as having good spreadability. △: 2 to 3 panelists rated the spreadability as good. ×: One or less panelists evaluated that the spreadability was good. (Criteria for determining which finger to use) ○: Four or more panelists rated which finger was best. △: Two or more but three panelists rated which finger was best. ×: One or less panelists rated which finger was better. (Criteria for determining wrinkles) ○: One or less panelists evaluated that there was wrinkle. △: Two or more but three or less panelists evaluated that there was wrinkle. ×: Four or more panelists evaluated that there was wrinkle. The properties and feel of each composition were observed and the results are shown in Table 2 below.
[0046] [Table 1]
[0047] [Table 2]
[0048] As shown by the fact that the shape retention of Control 1 and Control 2 in Table 2 was evaluated as "×," when ionic synthetic water-soluble polymers, carboxyl vinyl polymer or acrylic acid / alkyl methacrylate copolymer, were added instead of the nonionic synthetic water-soluble polymer (PEG-240 / decyltetradeceth-20 / HDI) copolymer, no gel was formed in any of the compositions; that is, no gel shape retention was observed. On the other hand, as shown by the fact that the shape retention of Compositions 1 to 7 was evaluated as "○," when the nonionic synthetic water-soluble polymer (PEG-240 / decyltetradeceth-20 / HDI) copolymer was added, gel was formed in all of the compositions; that is, gel shape retention was confirmed. Furthermore, in the case of Composition 8, which did not contain the (PEG-240 / decyltetradeceth-20 / HDI) copolymer, although a viscous solution was formed, no gel was formed, and the shape retention was evaluated as "×." These results confirmed that the incorporation of a non-ionic synthetic water-soluble polymer (PEG-240 / decyltetradeceth-20 / HDI) copolymer is necessary for gel formation. This is supported by the fact that Control 3 and Control 4, which contain a non-ionic synthetic water-soluble polymer (PEG-240 / decyltetradeceth-20 / HDI) copolymer, were also rated as "good" for shape retention.
[0049] However, the feel of use of Controls 3 and 4, which contained sorbitol or trehalose instead of the natural water-soluble polysaccharide stearoxyhydroxypropylmethylcellulose, and Composition 1, which did not contain the natural water-soluble polysaccharide stearoxyhydroxypropylmethylcellulose, was evaluated as "×" in all of the tested criteria of "moisture," "spreadability on skin," "finger runoff," and "smearing," and was therefore poor. On the other hand, Compositions 2 to 8, which contained 0.1 to 5% by mass of stearoxyhydroxypropylmethylcellulose, were evaluated as "○" in all of the criteria of "spreadability on skin," "finger runoff," and "smearing." Furthermore, with regard to the "freshness" of the feel during use, Composition 2, which contained 0.1% by mass of stearoxyhydroxypropyl methylcellulose, and Composition 7, which contained 5% by mass of stearoxyhydroxypropyl methylcellulose, were rated "Fair." Composition 8, which contained 5% by mass of stearoxyhydroxypropyl methylcellulose but did not contain (PEG-240 / Decyltetradeceth-20 / HDI) copolymer, was rated "Poor." These results demonstrate that, with regard to feel during use, a concentration of stearoxyhydroxypropyl methylcellulose, a natural water-soluble polysaccharide, is preferably in the range of 0.1% to 5% by mass, and, particularly, with regard to "freshness," a concentration of 0.2% to 1% by mass is more preferable. Furthermore, it was confirmed that the improvement of feel during use requires the incorporation of a natural water-soluble polysaccharide such as stearoxyhydroxypropyl methylcellulose, rather than an oligosaccharide such as sorbitol or trehalose.
[0050] <Experiment 2: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative and evaluation of its properties and usability> Tests were conducted on the shape retention and usability of L-ascorbic acid derivative-containing gel compositions for external use on the skin, varying the type of natural water-soluble polysaccharide.
[0051] <Experiment 2-1: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative> Aqueous solutions of natural water-soluble polysaccharides were prepared in the same manner as in Experiment 1-1, except that xanthan gum (trade name "Echogum T / Keltrol T," sold by DSP Gokyo Food & Chemical Co., Ltd.), guar gum (trade name "SUPERGEL CSA 200 / 50," sold by Sansho Co., Ltd.), or locust bean gum (trade name "GENU GUM type RL-200-J," sold by Sansho Co., Ltd.) was used instead of stearoxyhydroxypropylmethylcellulose (trade name "Sangelose 60L") as the natural water-soluble polysaccharide. Compositions 9 to 16 were prepared. Their formulations are shown in Table 3. Specifically, for Compositions 9 to 13, the amount of PEG-240 / decyltetradeceth-20 / HDI copolymer was the same at 1.2% by mass, and the amount of xanthan gum was varied to 0, 0.1, 0.2, 0.5, or 1% by mass. Composition 14 contained no PEG-240 / decyltetradeceth-20 / HDI copolymer and contained 1% by mass of xanthan gum. Compositions 15 and 16 contained the same amount of PEG-240 / decyltetradeceth-20 / HDI copolymer at 1.2% by mass, and guar gum or locust bean gum was used instead of xanthan gum at a content of 0.2% by mass.
[0052] <Experiment 2-2: Evaluation of properties and usability of gel-type skin topical compositions containing L-ascorbic acid derivatives> The properties / shape retention and usability of compositions 9 to 16 obtained in Experiment 2-1 were evaluated in the same manner as in Experiment 1-2, and the results are shown in Table 4. Furthermore, the viscosity was measured as an evaluation of the properties of the compositions, and the results are also shown in Table 4. The viscosity of each composition was measured three times for each sample using a rheometer (MCP102, manufactured by Anton Paar) and a measuring jig CP-50-1-SN34132 under conditions of a shear rate of 10 l / s, 10 data points, and a measurement interval of 6 seconds, and the average value was calculated.
[0053] [Table 3]
[0054]
Table 4
[0055] As can be seen from the test results in Table 4, for compositions 9 to 13, which contained 1.2% by mass of PEG-240 / decyltetradeceth-20 / HDI copolymer, the "Properties / Viscosity," which numerically represents shape retention, showed nearly identical values regardless of the presence or absence of xanthan gum or the amount of xanthan gum added. Furthermore, all compositions were rated "Good" for "Properties / Shape Retention," confirming that a gel was formed and its shape was maintained. On the other hand, as can be seen from the results for composition 14, when no PEG-240 / decyltetradeceth-20 / HDI copolymer was added, a viscous solution was formed, but no gel was formed, and the "Properties / Shape Retention" was rated "Poor." This confirms that the inclusion of PEG-240 / decyltetradeceth-20 / HDI copolymer, a nonionic synthetic water-soluble polymer, enables the formation of a gel. As shown in Table 4, the feel of use of Composition 9, which does not contain xanthan gum, was evaluated as "×" in all of the categories of "moisture," "spreadability on skin," "finger slippage," and "slippage," indicating a poor feel. In contrast, Compositions 11 to 13, which contain xanthan gum in the range of 0.2 to 1% by mass, were evaluated as "○" in all of the categories of "moisture," "spreadability on skin," "finger slippage," and "slippage." On the other hand, Composition 10, which contains a relatively low amount of xanthan gum at 0.1% by mass, was evaluated as "○" in all of the categories of "moisture," "spreadability on skin," "finger slippage," and "slippage," but was evaluated as "△" in "moisture," indicating a somewhat inferior feel. Composition 14, which contained 1% by mass of xanthan gum but no PEG-240 / decyltetradeceth-20 / HDI copolymer, was rated "×" for "feeling of use (moisture)," indicating a somewhat inferior feel in use. Compositions 15 and 16, which contained 0.2% by mass of guar gum or locust bean gum instead of xanthan gum, exhibited similar properties in terms of viscosity as those containing xanthan gum, and were rated "good" for "shape retention." The feel in use was also rated "good" for all of the following: "feel of use of moisture," "spreadability on skin," "slippage on fingers," and "smudges."The above results indicate that, even when xanthan gum is used as a natural water-soluble polysaccharide, as in the case of using stearoxyhydroxypropylmethylcellulose, in order to obtain a better feel when used, the blending concentration is preferably in the range of 0.1% to 1% by mass, and more preferably in the range of 0.2% to 1% by mass. Furthermore, it is shown that guar gum and locust bean gum can also be preferably used as natural water-soluble polysaccharides.
[0056] The results in Tables 2 and 4 show that although a gel can be formed by adding a nonionic synthetic water-soluble polymer (PEG-240 / decyltetradeceth-20 / HDI) copolymer to a topical skin composition containing ascorbic acid 2-glucoside, the gel feels poor when used. However, the feel when used is significantly improved by adding a natural water-soluble polysaccharide such as stearoxyhydroxypropylmethylcellulose, or a natural water-soluble polysaccharide such as xanthan gum, guar gum, or locust bean gum in combination with the gel.
[0057] <Experiment 3: Storage stability test of gel-type skin topical composition containing L-ascorbic acid derivative> A storage stability test was carried out on the L-ascorbic acid derivative-containing gel composition for external use on skin.
[0058] <Experiment 3-1: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative for storage stability testing> To test storage stability, L-ascorbic acid derivative-containing gel compositions for topical skin application 17 and 18 (hereinafter simply referred to as "Compositions 17 and 18") were prepared in the same manner as in Experiment 1-1, except that 10% by weight of sodium hydroxide was replaced with 10% by weight of potassium hydroxide. Their formulations are shown in Table 5. For Compositions 17 and 18, the blending amount of (PEG-240 / decyltetradeceth-20 / HDI) copolymer was 1.2% by weight, and the blending amount of stearoxyhydroxypropylmethylcellulose was 0.2 or 0.3% by weight. Controls 5 and 6 were prepared in the same manner as Compositions 17 and 18, except that they did not contain ascorbic acid 2-glucoside or 10% by weight of potassium hydroxide. Immediately after preparation, 110 mL of each composition and each control was filled into a 4 cm diameter, 12 cm high transparent glass bottle with a screw cap, sealed, and stored for 3 months in an incubator (CSH-111, manufactured by Espec Corporation) set at 40°C. After storage, the stability of each composition and each control was evaluated over time immediately after preparation, after 1 month of storage, and after 3 months of storage.
[0059] <Experiment 3-2: Evaluation of properties and usability of gel-type skin topical compositions containing L-ascorbic acid derivatives for storage stability testing> After storage at 40°C for a predetermined period, each composition and Controls 5 and 6 were evaluated for stability by evaluating their properties and usability. The properties were evaluated based on viscosity, pH, color, and shape retention. Viscosity and shape retention were evaluated in the same manner as in Experiment 2-2. pH was measured using a pH meter. Color was observed visually. The usability was evaluated based on freshness, spreadability on the skin, fingertip slippage, and creasing, and was evaluated in the same manner as in Experiment 1-2. The results are summarized in Table 6.
[0060] [Table 5]
[0061] [Table 6]
[0062] As shown in the results of the property evaluation of Compositions 17 and 18 in Table 6, even in the presence of ascorbic acid 2-glucoside, the incorporation of PEG-240 / decyltetradeceth-20 / HDI copolymer and stearoxyhydroxypropylmethylcellulose confirmed that the "properties / viscosity" of both compositions did not decrease from immediately after preparation to 1 month and 3 months of storage at 40°C. Furthermore, the "properties / shape retention" was also rated "Good," indicating that a gel was formed and its shape was maintained. This shape retention was also rated "Good," and was maintained not only immediately after preparation but also after 1 month and 3 months of storage at 40°C. Furthermore, no change in the pH of Compositions 17 and 18 was observed from immediately after preparation to 3 months of storage at 40°C, confirming that the properties of the compositions remained stable over that period. Furthermore, no discoloration of Compositions 17 and 18 was observed from immediately after preparation until after 3 months of storage at 40°C, confirming that the properties of the compositions remained unchanged and stable over that period.
[0063] On the other hand, as shown in Table 6, even in the presence of ascorbic acid 2-glucoside, the feel during use (freshness, spreadability on the skin, fingertip slippage, and smudging) of Compositions 17 and 18, which contained PEG-240 / decyltetradeceth-20 / HDI copolymer and stearoxyhydroxypropylmethylcellulose, was rated as "Good" from immediately after preparation until 3 months after storage at 40°C, demonstrating that the feel was maintained well. The storage stability results for Compositions 17 and 18 were comparable in all evaluation items to those of Controls 5 and 6, which did not contain ascorbic acid 2-glucoside or 10% by mass potassium hydroxide aqueous solution.
[0064] The results in Table 6 demonstrate that topical skin compositions containing the ascorbic acid derivative ascorbic acid 2-glucoside, the nonionic synthetic water-soluble polymer (PEG-240 / decyltetradeceth-20 / HDI) copolymer, and the natural water-soluble polysaccharide stearoxyhydroxypropylmethylcellulose are remarkably superior in terms of shape retention, feel during use, and stability. Furthermore, even when an ascorbic acid derivative, which provides many physiological functions as a topical skin preparation, is contained, or when a salt necessary for neutralization is added, when used in combination with a nonionic synthetic water-soluble polymer and a natural water-soluble polysaccharide, the composition exhibits properties and feel during use that are equivalent to those of a topical skin composition that does not contain an ascorbic acid derivative.
[0065] <Experiment 4: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative and evaluation of its properties and usability> Tests were conducted to evaluate the properties and usability of L-ascorbic acid derivative-containing gel compositions for topical skin application by varying the composition ratio of the L-ascorbic acid derivative, nonionic synthetic water-soluble polymer, and natural water-soluble polysaccharide.
[0066] <Experiment 4-1: Preparation of a gel-type skin topical composition containing an L-ascorbic acid derivative> Compositions 19 and 20 were prepared in the same manner as in Experiment 1-1, except that ascorbic acid 2-glucoside was used as the ascorbic acid derivative, PEG-240 / decyltetradeceth-20 / HDI copolymer was used as the nonionic synthetic water-soluble polymer, and a cellulose derivative was used as the natural water-soluble polysaccharide. The compositions are shown in Table 7. Specifically, for Composition 19, the amount of ascorbic acid 2-glucoside was 5% by mass, the amount of PEG-240 / decyltetradeceth-20 / HDI copolymer was 0.5% by mass, and the amount of stearoxyhydroxypropylmethylcellulose was 0.25% by mass. For Composition 20, the amount of ascorbic acid 2-glucoside was 0.01% by mass, the amount of PEG-240 / decyltetradeceth-20 / HDI copolymer was 1.0% by mass, and the amount of stearoxyhydroxypropylmethylcellulose was 0.5% by mass.
[0067] <Experiment 4-2: Evaluation of properties and usability of gel-type skin topical compositions containing L-ascorbic acid derivatives> The properties and usability of Compositions 19 and 20 obtained in Experiment 4-1 were evaluated in the same manner as in Experiment 2-2, and the results are shown in Table 8. The results for Composition 17 shown in Table 8 were copied from Table 6. For comparison, the "mass ratio" at the bottom of Table 8 has been added.
[0068] [Table 7]
[0069] [Table 8]
[0070] As can be seen from the test results in Table 8, in terms of properties, compared to the results of Composition 17 (mass ratio 1:0.6:0.1) prepared in Experiment 3, which contained 2% ascorbic acid 2-glucoside by mass, 1.2% by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer by mass, and 0.2% by mass of stearoxyhydroxypropylmethylcellulose (also shown in Table 8), the results of Composition 18 (mass ratio 1:0.6:0.1) prepared in Experiment 3, which contained 5% ascorbic acid 2-glucoside by mass, 0.5% by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer by mass, and 0.2% by mass of stearoxyhydroxypropylmethylcellulose (also shown in Table 8), Composition 19, which contained 0.25% by weight of ascorbic acid 2-glucoside (at a mass ratio of 1:0.1:0.05), had a low "Properties / Viscosity" value. Composition 20, which contained 0.01% by weight of ascorbic acid 2-glucoside, 1.0% by weight of PEG-240 / decyltetradeceth-20 / HDI copolymer, and 0.5% by weight of stearoxyhydroxypropylmethylcellulose (at a mass ratio of 1:100:50), had a high "Properties / Viscosity" value. However, both Compositions 19 and 20 were rated "Good" for "Properties / Shape Retention," confirming that a gel was formed and maintained its shape. Furthermore, the feel of the product was rated "Good" for all of the following criteria: "Moisturizing," "Spreadability on Skin," "Finger Slippage," and "Slippage." These results were comparable to those of Composition 17, prepared in Experiment 3. The above results indicate that the mass ratio of ascorbic acid 2-glucoside, (PEG-240 / decyltetradeceth-20 / HDI) copolymer, and stearoxyhydroxypropylmethylcellulose is preferably within the range of 1:0.1 to 100:0.05 to 50, respectively.
[0071] The results in Table 8 demonstrate that in a topical skin composition containing ascorbic acid 2-glucoside, when ascorbic acid 2-glucoside, a nonionic synthetic water-soluble polymer, and a natural water-soluble polysaccharide are blended in a mass ratio per dry solid content in the range of 1:0.1 to 100:0.05 to 50, the composition has excellent shape retention and a pleasant feel when used.
[0072] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. [Example]
[0073] <Whitening gel composition for external use on the skin> A whitening gel composition for topical skin application was obtained by uniformly mixing 85 parts by mass of deionized water with 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 4 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-730" sold by ADEKA Corporation) as a nonionic synthetic water-soluble polymer, 0.2 parts by mass of stearoxyhydroxypropylmethylcellulose (trade name "Sangelose 60L" sold by Daido Chemical Industry Co., Ltd.) as a natural water-soluble polysaccharide, 2 parts by mass of citrate buffer, 2.5 parts by mass of pentylene glycol (trade name "HYDROLITE-5" sold by Symrise Co., Ltd.), and appropriate amounts of 10% by mass sodium hydroxide solution. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making this an extremely stable whitening gel composition for topical skin application. [Example]
[0074] <Whitening gel composition for external use on the skin> A whitening gel composition for topical application to the skin was obtained by uniformly mixing 70 parts by mass of deionized water with 10 parts by mass of ascorbic acid 2-glucoside sodium salt (manufactured by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 1 part by mass of (PEG-240 / Decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-700" sold by ADEKA Corporation) as a nonionic synthetic water-soluble polymer, 1 part by mass of stearoxyhydroxypropylmethylcellulose (trade name "SANGELOSE 90L" sold by Daido Chemical Industry Co., Ltd.) as a natural water-soluble polysaccharide, 10 parts by mass of 1,3-butylene glycol (trade name "1,3-butylene glycol" sold by Daicel Corporation), 2 parts by mass of citrate buffer solution, 0.8 parts by mass of phenoxyethanol (trade name "HISOLV EPH" sold by TOHO CHEMICAL CO., LTD.), and appropriate amounts of 10% by mass potassium hydroxide solution. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making this an extremely stable whitening gel composition for topical skin application. [Example]
[0075] <Whitening gel composition for external use on the skin> In 60 parts by mass of deionized water, 5 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) and 5 parts by mass of ascorbic acid 2-glucoside potassium salt (manufactured by Hayashibara Co., Ltd.) as ascorbic acid derivatives, 4 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-730" sold by ADEKA Co., Ltd.) as a non-ionic synthetic water-soluble polymer, and xanthan gum as a natural water-soluble polysaccharide. A whitening gel-type topical skin composition was obtained by uniformly mixing 1 part by weight of gum (trade name "Echo Gum / Keltrol T," sold by DSP Gokyo Food & Chemical Co., Ltd.), 10 parts by weight of glycerin (trade name "Concentrated Glycerin for Cosmetics," sold by Kao Corporation), 10 parts by weight of 1,3-butylene glycol (trade name "1,3-butylene glycol," sold by Daicel Corporation), 2 parts by weight of citrate buffer, 2.5 parts by weight of pentylene glycol (trade name "HYDROLITE-5," sold by Symrise Co., Ltd.), and 10% by weight of potassium hydroxide solution. The properties of the composition were tested immediately after preparation and after 3 months of storage at 40°C in the same manner as in Experiment 3. The results showed that the composition had good shape retention and feel when used (freshness, spreadability on the skin, finger slippage, and ease of creasing). Even after 3 months of storage, the shape retention and feel when used were maintained, making it an extremely stable whitening gel-type topical skin composition. [Example]
[0076] <Moisturizing gel composition for external use on skin> A moisturizing gel-type composition for topical skin application was obtained by uniformly mixing 89.4 parts by mass of deionized water with 0.01 parts by mass of ascorbic acid 2-glucoside (trade name "Ascofresh®", sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 1 part by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "Adekanol GT-700", sold by ADEKA Corporation) as a nonionic synthetic water-soluble polymer, 0.1 parts by mass of tamarind gum (trade name "Glorid 6C", sold by DSP Gokyo Food & Chemical Co., Ltd.) as a natural water-soluble polysaccharide, 5 parts by mass of trehalose (trade name "Trehalose (for cosmetics)", sold by Hayashibara Co., Ltd.), 2 parts by mass of citrate buffer solution, and 2.5 parts by mass of pentylene glycol (trade name "HYDROLITE-5", sold by Symrise Co., Ltd.). In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making this an extremely stable moisturizing gel composition for topical skin use. [Example]
[0077] <Moisturizing gel composition for external use on skin> A moisturizing gel composition for topical skin application was obtained by uniformly mixing 90.9 parts by mass of deionized water with 0.1 parts by mass of sodium ascorbate (trade name "Sodium Ascorbate", sold by BASF Japan Ltd.) as an ascorbic acid derivative, 4 parts by mass of polyvinyl alcohol (trade name "GOHSENOL EG-05C", sold by Mitsubishi Chemical Corporation) as a non-ionic synthetic water-soluble polymer, 0.1 parts by mass of hydroxyethyl cellulose (trade name "HEC CF-G", sold by Sumitomo Seika Chemicals Co., Ltd.) as a natural water-soluble polysaccharide, and 0.1 parts by mass of pullulan (trade name "Pullulan", sold by Hayashibara Co., Ltd.), 2 parts by mass of citrate buffer solution, and 2.8 parts by mass of pentylene glycol (trade name "HYDROLITE-5", sold by Symrise Co., Ltd.). In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making this an extremely stable moisturizing gel composition for topical skin use. [Example]
[0078] <Gel-type beauty serum> In 60 parts by mass of deionized water, 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 2 parts by mass of polyvinyl alcohol (trade name "GOHSENOL EG-05C" sold by Mitsubishi Chemical Corporation) as a non-ionic synthetic water-soluble polymer, 0.3 parts by mass of sodium alginate (trade name "Arge Colloid" sold by Yamakawa Trading Co., Ltd.) as a natural water-soluble polysaccharide, 8 parts by mass of sorbitol (trade name "Sorbitol Kao" sold by Kao Corporation), 5 parts by mass of 1,3-butylene glycol (trade name "1,3-butylene glycol" sold by Daicel Corporation), 7 parts by mass of PEG-6, PEG-32 (trade name "PEG#1500" sold by NOF Corporation), 1 part by mass of PEG-10 sorbitan laurate (trade name "Nonion LT-210" sold by NOF Corporation), 0.2 parts by mass of olive oil, and ethanol A gel-type beauty serum was obtained by uniformly mixing 7 parts by mass of citric acid buffer, 2 parts by mass of pentylene glycol (trade name "HYDROLITE-5", sold by Symrise Co., Ltd.), and appropriate amounts of 10% by mass potassium hydroxide solution. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C, and the results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making it an extremely stable gel-type beauty serum. [Example]
[0079] <Gel-type beauty serum> A mixture of 54.4 parts by mass of deionized water, 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 1 part by mass of ethylene oxide-propylene oxide block copolymer (trade name "Creagel Crystal AF" sold by Shima Boeki Co., Ltd.) as a non-ionic synthetic water-soluble polymer, and 1 part by mass of polyurethane (trade name "ADEKA NOL GT-930" sold by ADEKA Corporation), 0.1 parts by mass of pullulan (trade name "Pullulan" sold by Hayashibara Co., Ltd.) as a natural water-soluble polysaccharide, 7 parts by mass of polyglyceryl-2 isostearate (trade name "NIKKOL DGMIS" sold by Nikko Chemicals Co., Ltd.), and sorbeth-30 tetraoleate (trade name "NIKKOL GO-430NV, sold by Nikko Chemicals Co., Ltd.), 5 parts by mass of glycerin (trade name "Concentrated Glycerin for Cosmetics", sold by Kao Corporation), 4 parts by mass of dipropylene glycol (trade name "DPG", sold by Dow Chemical Japan Co., Ltd.), 6 parts by mass of dimethicone (trade name "SH200C", sold by Dow Chemical Japan Co., Ltd.), 5 parts by mass of cyclopentasiloxane (trade name "KF-995", sold by Shin-Etsu Chemical Co., Ltd.), 5 parts by mass of liquid paraffin (trade name "Moresco White P-70", sold by MORESCO Corporation), 2 parts by mass of citrate buffer solution, 2.5 parts by mass of pentylene glycol (trade name "HYDROLITE-5", sold by Symrise Co., Ltd.), and 10% by mass of potassium hydroxide solution were mixed uniformly in appropriate amounts to obtain a gel-type beauty serum. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making it an extremely stable gel-type beauty serum. [Example]
[0080] <Cooling gel composition for external use on skin> In 65 parts by mass of deionized water, 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 2 parts by mass of ethylene oxide-propylene oxide block copolymer (trade name "Creagel Crystal AF" sold by Shima Trading Co., Ltd.) and 2 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "Adekanol GT-730" sold by ADEKA Corporation) as non-ionic synthetic water-soluble polymers, 0.2 parts by mass of guar gum (trade name "SUPERGEL CSA200 / 50" sold by Sansho Co., Ltd.) as a natural water-soluble polysaccharide, 10 parts by mass of glycerin (trade name "Concentrated Glycerin for Cosmetics" sold by Kao Corporation), and ethanol A cooling gel composition for topical skin application was obtained by uniformly mixing 10 parts by weight of citric acid buffer, 0.1 parts by weight of menthol (trade name "L-Menthol", sold by Suzuki Menthol Co., Ltd.), 2 parts by weight of citrate buffer, 0.8 parts by weight of phenoxyethanol (trade name "Hisorb EPH", sold by Toho Chemical Co., Ltd.), and appropriate amounts of 10% by weight of potassium hydroxide solution. The properties were tested immediately after preparation and after 3 months of storage at 40°C in the same manner as in Experiment 3, and the results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making this an extremely stable cooling gel composition for topical skin application. [Example]
[0081] <Warming gel composition for external use on skin> A mixture of 84.9 parts by mass of deionized water and 0.1 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 1 part by mass of ethylene oxide-propylene oxide block copolymer (trade name "Creagel Crystal AF" sold by Shima Trading Co., Ltd.) as a non-ionic synthetic water-soluble polymer, and 0.5 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-700" sold by ADEKA Co., Ltd.), and xanthan gum (trade name "KELTROL A warming gel-type composition for topical skin application was obtained by uniformly mixing 0.2 parts by weight of "Glucosyl Hesperidin CG-BT" (sold by Sumitomo Seika Chemicals Co., Ltd.), 10 parts by weight of 1,3-butylene glycol (trade name "1,3-butylene glycol" sold by Daicel Corporation), 0.5 parts by weight of transglycosylated hesperidin (trade name "Alpha Glucosyl Hesperidin" sold by Hayashibara Co., Ltd.), 2 parts by weight of citrate buffer, and 0.8 parts by weight of phenoxyethanol (trade name "Hisorb EPH" sold by Toho Chemical Co., Ltd.). The properties of the composition were tested immediately after preparation and after 3 months of storage at 40°C in the same manner as in Experiment 3. The results showed that the composition had good shape retention and feel when used (freshness, spreadability on the skin, finger slippage, and smoothness). Even after 3 months of storage, the shape retention and feel when used were maintained, making it an extremely stable warming gel-type composition for topical skin application. [Example]
[0082] <Gel-type external skin composition for massage> A mixture of 70.8 parts by mass of deionized water, 2 parts by mass of trehalose (trade name "Treha", sold by Hayashibara Co., Ltd.), 0.1 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark), sold by Hayashibara Co., Ltd.)) as an ascorbic acid derivative, 4 parts by mass of polyvinyl alcohol (trade name "Gohsenol EG-05C", sold by Mitsubishi Chemical Corporation) as a non-ionic synthetic water-soluble polymer, 0.3 parts by mass of hydroxyethyl cellulose (trade name "HEC CF-W", sold by Sumitomo Seika Chemicals Co., Ltd.) as a natural water-soluble polysaccharide, and hyaluronic acid (trade name "Hyaluronic Acid San") was added. A gel-type topical skin massage composition was obtained by uniformly mixing 4 parts by weight of 1,3-butylene glycol (trade name "1,3-butylene glycol" sold by Daicel Corporation), 10 parts by weight of glycerin (trade name "Cosmetic Concentrated Glycerin" sold by Kao Corporation), 2 parts by weight of citrate buffer, and 0.8 parts by weight of phenoxyethanol (trade name "Hisorb EPH" sold by Toho Chemical Co., Ltd.). The properties of the composition were tested immediately after preparation and after 3 months of storage at 40°C in the same manner as in Experiment 3. The results showed that the composition had good shape retention and feel when used (freshness, spreadability on the skin, finger slippage, and smoothness). Even after 3 months of storage, the shape retention and feel when used were maintained, making it an extremely stable gel-type topical skin massage composition. [Example]
[0083] <Gel-type cleanser> 76.8 parts by mass of deionized water was mixed with 0.1 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 1 part by mass of ethylene oxide-propylene oxide block copolymer (trade name "Creagel Crystal AF" sold by Shima Trading Co., Ltd.) as a non-ionic synthetic water-soluble polymer, and hydroxyethyl cellulose (trade name "HEC A gel-like detergent was obtained by uniformly mixing 0.3 parts by mass of dipropylene glycol (trade name "DPG", sold by Dow Chemical Japan Co., Ltd.), 6 parts by mass of 1,3-butylene glycol (trade name "1,3-butylene glycol", sold by Daicel Corporation), 6 parts by mass of PEG-75 (trade name "PEG400", sold by NOF Corporation), 1 part by mass of POE(20) cocoyl methyl taurate Na (trade name "Neoscope CN-30", sold by Toho Chemical Industry Co., Ltd.), 2 parts by mass of citrate buffer solution, and 0.8 parts by mass of phenoxyethanol (trade name "Hisorb EPH", sold by Toho Chemical Co., Ltd.). In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making it an extremely stable gel-type cleanser. [Example]
[0084] <Gel-type UV protection agent> The mixture was 69.2 parts by mass of deionized water, 1 part by mass of magnesium ascorbyl phosphate (trade name "L-Ascorbyl Magnesium Phosphate", sold by Fujifilm Wako Pure Chemical Industries, Ltd.) as an ascorbic acid derivative, 3 parts by mass of polyurethane (trade name "Adekanol GT-930", sold by Mitsubishi Chemical Corporation) as a non-ionic synthetic water-soluble polymer, 1 part by mass of soluble dextrin (trade name "Fibrixa (registered trademark)", sold by Hayashibara Co., Ltd.) as a natural water-soluble polysaccharide, 10 parts by mass of cyclodextrin (trade name "CD102", sold by Rocket Japan Co., Ltd.), 5 parts by mass of 1,3-butylene glycol (trade name "1,3-butylene glycol", sold by Daicel Corporation), and polyglyceryl-10 stearate (trade name "NIKKOL Decaglyn A gel-type UV protection agent was obtained by uniformly mixing 3 parts by mass of "Hysorb EPH", sold by Nikko Chemicals Co., Ltd.), 3 parts by mass of titanium dioxide (trade name "Titanium Dioxide", sold by Ishihara Sangyo Kaisha), 2 parts by mass of citrate buffer, and 0.8 parts by mass of phenoxyethanol (trade name "Hysorb EPH", sold by Toho Chemical Co., Ltd.). The properties were tested in the same manner as in Experiment 3 immediately after preparation and after 3 months of storage at 40°C. Results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger slippage, and crease-free) were good, and the shape retention and feel in use were maintained even after 3 months of storage, making it an extremely stable gel-type UV protection agent. [Example]
[0085] <Gel-type wash-off pack> A gel-like rinse pack was obtained by uniformly mixing 81.1 parts by mass of deionized water with 0.1 parts by mass of sodium ascorbyl phosphate (trade name "Sodium L-Ascorbyl Phosphate", sold by BASF Japan Ltd.) as an ascorbic acid derivative, 5 parts by mass of polyvinyl alcohol (trade name "Gohsenol EG-05C", sold by Mitsubishi Chemical Corporation) as a non-ionic synthetic water-soluble polymer, 1 part by mass of locust bean gum (trade name "Phytaluronate PF", sold by DSM Nutrition Japan Co., Ltd.) as a natural water-soluble polysaccharide, 10 parts by mass of sorbitol (trade name "Sorbitol Kao", sold by Kao Corporation), 2 parts by mass of citrate buffer solution, and 0.8 parts by mass of phenoxyethanol (trade name "Hisorb EPH", sold by Toho Chemical Co., Ltd.). In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the shape retention and feel in use (freshness, spreadability on the skin, finger smoothness, and crease-free) were good. Even after 3 months of storage, the shape retention and feel in use were maintained, making this an extremely stable gel-type rinse-off pack. [Example]
[0086] <Whitening gel composition for external use on the skin> A whitening gel composition for topical skin application was obtained by uniformly mixing 79.3 parts by mass of deionized water with 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 4 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-730" sold by ADEKA Corporation) as a nonionic synthetic water-soluble polymer, 0.2 parts by mass of stearoxyhydroxypropylmethylcellulose (trade name "Sangelose 60L" sold by Daido Chemical Industry Co., Ltd.) as a natural water-soluble polysaccharide, 10 parts by mass of diethoxyethyl succinate (trade name "Crodamol DES-LQ-(JP)" sold by Croda Japan Co., Ltd.), 2 parts by mass of citrate buffer, 2.5 parts by mass of pentylene glycol (trade name "HYDROLITE-5" sold by Symrise Co., Ltd.), and appropriate amounts of 10% by mass sodium hydroxide solution. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the product had good shape retention and feel in use (freshness, spreadability on the skin, finger smoothness, and crease-free), as well as good transparency upon application. Even after 3 months of storage, the product maintained its shape retention, feel in use, and transparency upon application, making it an extremely stable whitening gel composition for topical skin application. [Example]
[0087] <Whitening gel composition for external use on the skin> A whitening gel composition for topical skin application was obtained by uniformly mixing 74.3 parts by mass of deionized water with 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 4 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-730" sold by ADEKA Corporation) as a nonionic synthetic water-soluble polymer, 0.2 parts by mass of stearoxyhydroxypropylmethylcellulose (trade name "SANGELOSE 60L" sold by Daido Chemical Industry Co., Ltd.) as a natural water-soluble polysaccharide, 5 parts by mass of diethoxyethyl adipate (sold by Fujifilm Wako Pure Chemical Industries, Ltd.), 10 parts by mass of ethanol, 2 parts by mass of citrate buffer solution, 2.5 parts by mass of pentylene glycol (trade name "HYDROLITE-5" sold by Symrise Co., Ltd.), and appropriate amounts of 10% by mass sodium hydroxide solution. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the product had good shape retention and feel in use (freshness, spreadability on the skin, finger smoothness, and crease-free), as well as good transparency upon application. Even after 3 months of storage, the product maintained its shape retention, feel in use, and transparency upon application, making it an extremely stable whitening gel composition for topical skin application. [Example]
[0088] <Whitening gel composition for external use on the skin> A whitening gel composition for topical skin application was obtained by uniformly mixing 76.8 parts by mass of deionized water with 2 parts by mass of ascorbic acid 2-glucoside (trade name "AA2G (registered trademark)" sold by Hayashibara Co., Ltd.) as an ascorbic acid derivative, 4 parts by mass of (PEG-240 / decyltetradeceth-20 / HDI) copolymer (trade name "ADEKA NOL GT-730" sold by ADEKA Corporation) as a nonionic synthetic water-soluble polymer, 0.2 parts by mass of stearoxyhydroxypropylmethylcellulose (trade name "SANGELOSE 60L" sold by Daido Chemical Industry Co., Ltd.) as a natural water-soluble polysaccharide, 2.5 parts by mass of diethoxyethyl sebacate (sold by Kanto Chemical Co., Ltd.), 10 parts by mass of ethanol, 2 parts by mass of citrate buffer solution, 2.5 parts by mass of pentylene glycol (trade name "HYDROLITE-5" sold by Symrise Co., Ltd.), and appropriate amounts of 10% by mass sodium hydroxide solution. In the same manner as in Experiment 3, the properties were tested immediately after preparation and after 3 months of storage at 40°C. The results showed that the product had good shape retention and feel in use (freshness, spreadability on the skin, finger smoothness, and crease-free), as well as good transparency upon application. Even after 3 months of storage, the product maintained its shape retention, feel in use, and transparency upon application, making it an extremely stable whitening gel composition for topical skin application.
Claims
1. L-ascorbic acid derivatives, One or two kinds of nonionic synthetic water-soluble polymers selected from (PEG-240 / decyltetradeceth-20 / HDI) copolymer and ethylene oxide-propylene oxide block copolymer, and The gel composition for external use on the skin contains one or more natural water-soluble polysaccharides selected from the group consisting of soluble cellulose, guar gum, tamarind gum, soluble starch, and cyclodextrin.
2. 2. The gel composition for external application to the skin according to claim 1, wherein the L-ascorbic acid derivative is L-ascorbic acid 2-glucoside.
3. 3. The gel composition for external application to the skin according to claim 1, which has excellent shape retention, feel during use, and stability.
4. 4. A gel-like composition for external use on the skin according to any one of claims 1 to 3, wherein the mass ratio of the L-ascorbic acid derivative, the nonionic synthetic water-soluble polymer, and the natural water-soluble polysaccharide per dry solid content is 1:0.01-500:0.01-500.
5. 5. The gel composition for external application to skin according to claim 1, further comprising a polyoxyethylene dicarboxylic acid ester.
6. 6. The gel composition for external application to the skin according to claim 5, wherein the polyoxyethylene dicarboxylate ester is one or more selected from the group consisting of diethoxyethyl succinate, diethoxyethyl adipate and diethoxyethyl sebacate.
Citation Information
Patent Citations
External skin preparation for whitening
JP2002284664A
Water-containing gel material, method for producing the water-containing gel material and use of the same
JP2004075672A
Skin care preparation for external use
JP2005068023A
Composition for external application
JP2005132828A
External preparation for skin useful for preventing sebum shininess
JP2006063032A